Practical use of portfolio risk management today - Roxburgh, Daryl (Henry Stewart Talks, 2007)
Definitions of risk management (RM) in different contexts, Practical application rather than theory, Does RM make a major contribution to portfolio safety?, Can RM exacerbate adverse markets?, The impacts of regulatory risk on fund managers, Appropriate or mist-targeted?, How is risk forecast and how does that feed into the investment process?, Do quantitative techniques add value or lower risk?, Risk strategies: how to measure, implement and control
Archived at 2022/04/04